Cervical Ectopic Pregnancy - Maradiegue, Eduardo (2015)
Cervical ectopic pregnancy is one of the rarest forms of ectopic pregnancy. Fahmy reported that the frequency is 1 in 9,575 births -152.219, however, some authors report that is much more frequent since there are cases that are not reported or are not diagnosed.